2022
DOI: 10.3390/molecules27217549
|View full text |Cite
|
Sign up to set email alerts
|

Process and Anti-Mildew Properties of Tea Polyphenol-Modified Citral-Treated Bamboo

Abstract: In order to reduce the oxidative degradation of citral, our research group modified citral with the natural antioxidant from tea polyphenols and applied it to bamboo processing to enhance the anti-mold effect of bamboo, but its application to the bamboo treatment process and the anti-mold effect is still not clear. For this reason, in this paper, the tea polyphenol-modified citral anti-mildew treatment of bamboo as well as the anti-mildew properties of bamboo were explored using the orthogonal testing method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In order to enhance the mildew resistance of bamboo, Chen et al modified citral and applied it to bamboo processing [51]. The results showed that the resistance rate of modified bamboo to common mold could reach 100%.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…In order to enhance the mildew resistance of bamboo, Chen et al modified citral and applied it to bamboo processing [51]. The results showed that the resistance rate of modified bamboo to common mold could reach 100%.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Chinese herbal medicines, as natural products, are safer compared to chemically synthesized antimicrobial drugs [ 10 , 11 , 12 ]. The components of Chinese herbal medicines are extremely complex, and the extraction and separation of their active antimicrobial ingredients can improve the efficiency of mildew inhibitors [ 13 , 14 , 15 , 16 ]. Some Chinese herbal medicines have identified antimicrobial monomers [ 17 , 18 , 19 ] and determined their chemical structures [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%